ANALISIS RETURN SAHAM PERUSAHAAN SUB SEKTOR METALS & MINERALS DI BURSA EFEK INDONESIA - Aulia Rini Puspitasari; Nurjanti Takarini (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The dynamics of the capital market encourage investors to pay closer attention to corporate financial indicators when determining stock returns, particularly in the Basic Materials sector, Metals & Minerals sub-sector, which is characterized by relatively high volatility. This study aims to analyze the effect of profitability, liquidity, and leverage on stock returns of Metals & Minerals companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The population of this study consists of all companies within the Metals & Minerals sub-sector listed on the Indonesia Stock Exchange, while the sample was selected using a purposive sampling method based on predetermined criteria, resulting in a number of eligible companies. Multiple linear regression analysis was employed using secondary data obtained from the companies’ annual financial reports. The results indicate that profitability has a significant effect on stock returns, whereas liquidity and leverage do not have a significant effect on stock returns. These findings suggest that a company's ability to generate profits is a key factor considered by investors in making investment decisions. The managerial implication of this study is the importance of improving profitability to attract investors and enhance firm value. The limitation of this study lies in the use of specific financial variables and the sample scope, which is limited to a single industry sub-sector.